Feasibility Study of Granting Legal Personality to ‎Bankrupt Estate (Studying the Iranian and American ‎Law)‎ - Habib Ramezani Akerdi (پژوهش های حقوق تطبیقی, 2022)
After the issuance of the bankruptcy order, the general rules are disassembled; for example, the bankrupt does not have the right to intervene in the property, and raise an action regarding his debts, claims and property is done by the trustee and the response to the claims is also done by him. It is also possible to continue the bankrupt business by others. One of the important questions raised by the total regulations governing bankruptcy is how to justify the legal relationship between the merchant and the creditors with the property, as well as the legal status of debts and claims. Various theories have been proposed in response, one of the most important of which has been noticed in American law is the theory of granting legal personality to the property (property, debts and claims) of the bankrupt at the time of issuing the bankruptcy order. According to this theory, it becomes possible to justify "the rule of prohibition of intervention", "the legal position of the trustee institution", “the possibility of continuing the bankrupt business after the issuance of the bankruptcy order without creating a conflict with the rights of creditors” and “the fall of excess debt over assets". Examining the rules governing bankruptcy in Iranian and American law shows that although some legal rules can be justified based on this theory, they have not been accepted by the legislator.